2022
DOI: 10.1272/jnms.jnms.2022_89-512
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 8 Years of Noninvasive Prenatal Testing at Nippon Medical School Hospital

Abstract: Background: Noninvasive prenatal testing (NIPT) is used to screen for fetal chromosomal abnormalities, such as fetal aneuploidy, and has been offered at our hospital since 2013. We analyzed data from our center to determine if NIPT screenees could be given more-accurate information on NIPT outcomes.Methods: This retrospective observational study included 819 pregnant women who requested NIPT at Nippon Medical School Hospital from November 2013 to October 2021. We examined medical records for data on NIPT resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Our results showed that clients who wished to undergo NIPT or combined tests changed their choice or canceled testing after GC. GC is considered to have a significant impact on the choice of prenatal genetic testing 1,7,15 ; however, in Japan, the impact of GC on the choice of prenatal genetic testing has not been significant in clients who wished to undergo NIPT 9,16 . In this study, more couples did not select NIPT after GC, as opposed to a previous study 16 .…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Our results showed that clients who wished to undergo NIPT or combined tests changed their choice or canceled testing after GC. GC is considered to have a significant impact on the choice of prenatal genetic testing 1,7,15 ; however, in Japan, the impact of GC on the choice of prenatal genetic testing has not been significant in clients who wished to undergo NIPT 9,16 . In this study, more couples did not select NIPT after GC, as opposed to a previous study 16 .…”
Section: Discussioncontrasting
confidence: 55%
“…GC is considered to have a significant impact on the choice of prenatal genetic testing 1,7,15 ; however, in Japan, the impact of GC on the choice of prenatal genetic testing has not been significant in clients who wished to undergo NIPT. 9,16 In this study, more couples did not select NIPT after GC, as opposed to a previous study. 16 This is the major difference between the findings of our study and those of previous reports, because in previous studies, clients may have seen at the unfamiliar facilities where NIPT would be conducted without the knowledge and the availability of other options.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation